Plant Production through Adventive Organogenesis of Mature Pistachio, Pistacia vera L. Cultivars 'Atli' and 'Siirt' - Tilkat, E.; Akdemir, H.; Ozden-Tokatli, Y.; Yildirim, H.; Suzerer, V.; Onay, A. (Int Soc Horticultural Science, 2011)
A method was developed for direct plant regeneration from in vitro-derived leaf explants of Pistacia vera L. cvs. Siirt and Atli. The in vitro adventive organogenesis involved six steps that included (1) explant disinfection, (2) the addition of cytokinins (benzyladenine; BA, Kinetin; Kin) for the in vitro installation of mature shoot tips, and the successful rapid proliferation of shoot initials, (3) induction of shoot initials from the regenerated mature leaves, (4) regeneration and elongation of shoots from the shoot initials, (5) rooting of the shoots and (6) acclimatization of the plantlets. Exudation of phenolics was not observed when the rinsed shoot tips were washed twice, in sterile distilled water, on a shaker at 150 rpm for 1 hour. Explants on the Murashige & Skoog (MS) medium with Gamborg vitamins supplemented with 1 mg L-1 BA produced the highest number of shoots and longest shoots in the second step. Leaves excised from axenic shoot cultures of pistachio were used to induce adventive organogenesis on a MS medium with Gamborg vitamins supplemented with combinations of different concentrations and combination of BA and indole-3-acetic acid (IAA). In the third stage, the best medium for shoot induction in both cultivars was MS medium with 1 mg L-1 IAA and 2 mg L-1 BA. For shoot multiplication, the highest number of new microshoot/ explants for male and female was obtained in a culture medium supplemented with 1 mg L-1 BA, but it was not significantly different from the number obtained at 2 mg L-1 BA in the fourth step. The elongated shoots (>4 cm long) were rooted on a full-strength MS basal medium supplemented with 2 mg L-1 of indole-3-butyric acid (IBA) in the fifth step. Finally, the rooted plants were transferred to soil. This protocol could be utilized for in vitro clonal propagation of this economically important plant.
5th International Symposium on Pistachios and Almonds -- OCT 06-10, 2009 -- Univ Harran, Sanliurfa, TURKEY
Keywords: adventitous shoot multiplication; leaf culture; micropropagation; pistachio